2011
DOI: 10.1186/1751-0147-53-22
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the success of rabies vaccination of dogs in Sweden

Abstract: BackgroundUnited Kingdom, Ireland, Malta and Sweden maintain their national provisions for a transitional period regarding rules concerning rabies vaccination and individual serological test for rabies neutralizing antibodies. The purpose of vaccinating dogs against rabies is to establish pre-exposure immunity and protect individual animals from contracting rabies.The aim of the study was to investigate factors associated with reaching the internationally accepted threshold antibody titre of 0.5 IU/mL after ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 11 publications
(17 reference statements)
15
41
1
Order By: Relevance
“…In agreement with previously reported findings (Mansfield et al., ; Kennedy et al., ; Zanoni et al., ; Berndtsson et al., ), young dogs in our study showed a lower probability of achieving a positive outcome, with a steadily increasing success rate in adult dogs up to the age of 9 and declining thereafter. This finding is not unexpected, based on the dog immune system development and senescence (Day, , ) and previously reported evidence that rabies vaccination induces a significantly lower response in old dogs than in adult ones (12.1 ± 1.3 and 3.15 ± 0.8 years, respectively) (HogenEsch et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with previously reported findings (Mansfield et al., ; Kennedy et al., ; Zanoni et al., ; Berndtsson et al., ), young dogs in our study showed a lower probability of achieving a positive outcome, with a steadily increasing success rate in adult dogs up to the age of 9 and declining thereafter. This finding is not unexpected, based on the dog immune system development and senescence (Day, , ) and previously reported evidence that rabies vaccination induces a significantly lower response in old dogs than in adult ones (12.1 ± 1.3 and 3.15 ± 0.8 years, respectively) (HogenEsch et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…Of interest, it also includes an analysis of the observations collected from dogs entering the Italian border both from EU and non‐EU countries. Findings from our study are generally in agreement with those reported in the literature, identifying sex as the only variable not associated with serological response to rabies vaccination in dogs (Cliquet et al., ; Mansfield et al., ; Kennedy et al., ; Zanoni et al., ; Berndtsson et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this was the first study to correlate a poor rabies-specific vaccine-induced immune response in obese humans. These data supported an animal study that indicated larger breeds of dogs had an increased risk for inadequate vaccine-induced rabies-specific antibody levels [83]. …”
Section: Rabies Infection and Vaccine-induced Antibody Response Insupporting
confidence: 78%
“…The age, size and breed of the dog and the type of vaccine, number of vaccinations and the interval(s) between vaccination influence the quantity and persistence of RABV-specific immunity (18–20). Based on these variables, the frequency of dogs that seroconvert after a single inoculation with inactivated RABV-based vaccines above 0.5 IU/ml varies widely from study to study and can range from 50% to >90% (18, 20–22). In dogs that do respond to vaccination with inactivated RABV-based vaccines, antibody titers peak around 2–4 weeks post-immunization and then rapidly decline (23).…”
Section: Discussionmentioning
confidence: 99%